Determination of polyamines in urine via electrospun nanofibers–based solid‐phase extraction coupled with GC‐MS and application to gastric cancer patients. Issue 3 (19th December 2022) - Xie, Li; Chen, Weilin; Shu, Qing; Xie, Wei; Bian, Linxiao; Deng, Guozhe; Kang, Xuejun; Ge, Weihong
Abstract : The simultaneous determination of polyamines and their metabolites in urine samples was achieved by gas chromatography–mass spectrometry in the selected ion monitoring mode. After conjugating with the ion‐pair reagent bis‐2‐ethylhexylphosphate in the aqueous phase, the polyamines in the samples were extracted with polystyrene nanofiber‐based packed‐fiber solid‐phase extraction followed by a derivatization step using pentafluoropropionyl anhydride. With optimal conditions, all analytes were separated well. For analytes of putrescine, cadaverine, N‐acetylputrescine, and N‐acetylcadaverine, the linearity was good in the range of 0.05–500 μmol/L ( R 2 ≥ 0.993). While for spermidine, spermine, acetylspermidine, N 8 ‐acetylspermidine, and N‐acetylspermine, the linearity was good in the range of 0.5–500 μmol/L ( R 2 ≥ 0.990). The recoveries of three spiked concentrations (0.5, 5, 300 μmol/L) were 85.6%–108.4%, and relative standard deviations for intra‐ and interday were in the range of 2.9%–13.4% and 4.5%–15.1%, respectively. The method was successfully applied to the analysis of urine samples of gastric cancer patients. The results showed that the levels of most polyamines and N‐acetylated polyamines from the patient group were significantly higher than those from the control group. The altered concentrations of the above‐mentioned metabolites suggest their role in the pathogenesis of gastric cancer, and they should be further evaluated as potential markers of gastric cancer.